PBL-Oriented E-LKPD Assisted by Liveworksheet for Improving Cognitive Outcomes in Fifth-Grade IPAS Learning (IJORER : International Journal of Recent Educational Research, 2026)
This study aims to develop an electronic student worksheet (E-LKPD) based on the Project-Based Learning (PBL) model assisted by Liveworksheet to improve the cognitive learning outcomes of fifth-grade elementary school students. The research employed a Research and Development (R&D) design using the ADDIE development model. The research subjects were fifth-grade students at SD Negeri 22 Rejang Lebong, with Class VA serving as the trial class and Class VB as the experimental class. Both qualitative and quantitative data were collected through observation, interviews, questionnaires, tests, and documentation. Data analysis involved qualitative and quantitative techniques. The findings show that: (a) the E-LKPD validation results by material, language, and graphic experts ranged from0.67 to 1.00, indicating valid to highly valid categories; (b) the test instrument validation results by material, language, and construction experts ranged from 0.72 to 0.90, also categorized as valid to highly valid; and (c) teacher and student responses were highly positive, with teacher response percentages ranging from 67% to 100% and student responses from 87% to 93%. The average N-gain score of the experimental class was 0.8 (80.9%), indicating a high level of effectiveness. Therefore, the PBL-based E-LKPD assisted by Liveworksheet is declared valid, feasible, and effective for use as an instructional material to improve students’cognitive learning outcomes in the ecosystem topic, particularly the food-chain subtopic.